Composite high order super-twisting sliding mode control algorithm for PMSMs based on dung beetle optimization - Wang, Yi; Shi, Song; Mai, Songping (JOURNAL OF POWER ELECTRONICS, 2025)
In permanent magnet synchronous motors (PMSMs) employing super-twisting sliding mode controllers, integral operations are often used to mask discontinuous signals and reduce chattering. However, this strategy falls short in addressing the chattering caused by high-frequency switching signals and does not significantly enhance disturbance suppression. Additionally, the complexity of the control algorithm poses challenges in parameter tuning. This paper introduces a composite high-order super-twisting sliding mode (HOSTSM) controller designed to minimize chattering and improve the disturbance resistance when compared to traditional super-twisting sliding mode controllers. The proposed controller employs adjustable high-order integrals to replace high-frequency switching components, which improves the control continuity and reduces chattering. A sigmoid function is used in place of the traditional discontinuous sign function, further mitigating chattering. Moreover, a sliding mode disturbance observer (SMDO) is integrated to dynamically adjust the output of the controller by estimating the real-time load torque, enhancing its disturbance rejection capabilities. The dung beetle optimization (DBO) method is utilized for parameter tuning, leveraging a specific fitness function to achieve optimal offline parameter adjustment of the controller. Experimental results demonstrate significant improvements in the HOSTSM + SMDO composite sliding mode speed controller optimized via the DBO method, showing a 31.8% reduction in the maximum overshoot and a 60.0% decrease in the settling time. These advances contribute to an improved dynamic response and heightened disturbance resistance, which markedly enhances the overall control performance. This underscores the effectiveness of the controller in challenging control environments.